Cognitive Intervention for Attention and Executive Function Impairments in Children With Traumatic Brain Injury: A Pilot Study. Issue 6 (November 2016) - Treble-Barna, Amery; Sohlberg, McKay Moore; Harn, Beth E.; Wade, Shari L.
Abstract : Objective: To test the effectiveness of the Attention Improvement and Management (AIM) program, a cognitive intervention for improving impairments in attention and executive functions (EFs) after pediatric traumatic brain injury (TBI). Setting: Tertiary care children's hospital. Participants: A total of 13 children with complicated mild-to-severe TBI (average of 5 years postinjury) and 11 healthy comparison children aged 9 to 15 years completed the study. Design: Open-label pilot study with a nontreated control group. Main Measures: Subtests from the Test of Everyday Attention-for Children (TEA-Ch) and the Delis–Kaplan Executive Function System (D-KEFS), the self- and parent-report from the Behavior Rating Inventory of Executive Function (BRIEF), and the Goal Attainment Scale (GAS). Results: Relative to the healthy comparison group, children with TBI demonstrated significant improvement postintervention on a neuropsychological measure of sustained attention, as well as on parent-reported EFs. The majority of families also reported expected or more-than-expected personalized goal attainment. Conclusions: The study provides preliminary evidence for the effectiveness of AIM in improving parent-reported EFs and personalized real-world goal attainment in children with TBI. Abstract : Supplemental Digital Content is Available in the Text.